Academic Procrastination in Undergraduate Students: Understanding the Role of Basic Psychological Need Satisfaction and Frustration and Academic Motivation - Oram, Rylee; Rogers, Maria (Canadian Journal of Education / Revue canadienne de l'éducation)

(untitled) (Canadian Society for the Study of Education, 2022)
Procrastination is particularly prevalent in the post-secondary student population, with prevalence rates ranging between 70–95%. Students have consistently cited motivation, or a lack thereof, as one of the main sources of their procrastination. One of the most prominent theories explaining motivation is self-determination theory (SDT). Despite the direct links between motivation and procrastination, procrastination has been scarcely examined through the lens of SDT. The current study examined the relationship between basic psychological need (BPN), satisfaction and frustration, academic motivation, and academic procrastination. A sample of 617 undergraduate students completed an online questionnaire about their university experience. Data were analyzed using mediational structural equation models. Results suggested that academic motivation significantly mediated the relationship between BPN satisfaction and procrastination, but not the relationship between BPN frustration and procrastination. These results demonstrate the importance of satisfying the BPN of undergraduate students, as it may increase their academic motivation and, subsequently, reduce their procrastination.